ABI1 and PP2CA Phosphatases Are Negative Regulators of Snf1-Related Protein Kinase1 Signaling in Arabidopsis - Rodrigues, A. (2016)
Plant survival under environmental stress requires the integration of multiple signaling pathways into a coordinated response, but the molecular mechanisms underlying this integration are poorly understood. Stress-derived energy deprivation activates the Snf1-related protein kinases1 (SnRK1s), triggering a vast transcriptional and metabolic reprogramming that restores homeostasis and promotes tolerance to adverse conditions. Here, we show that two clade A type 2C protein phosphatases (PP2Cs), established repressors of the abscisic acid (ABA) hormonal pathway, interact with the SnRK1 catalytic subunit causing its dephosphorylation and inactivation. Accordingly, SnRK1 repression is abrogated in double and quadruple pp2c knockout mutants, provoking, similarly to SnRK1 overexpression, sugar hypersensitivity during early seedling development. Reporter gene assays and SnRK1 target gene expression analyses further demonstrate that PP2C inhibition by ABA results in SnRK1 activation, promoting SnRK1 signaling during stress and once the energy deficit subsides. Consistent with this, SnRK1 and ABA induce largely overlapping transcriptional responses. Hence, the PP2C hub allows the coordinated activation of ABA and energy signaling, strengthening the stress response through the cooperation of two key and complementary pathways.